THE ROLE OF INTERPERSONAL COMMUNICATION IN IMPROVING THE EFFECTIVENESS OF STUDENT–LECTURER RELATIONSHIPS: A LITERATURE REVIEW - Amalia Fitri Syahira; Muhammad Abidzar Alghifari; Dzaky Ismi Arifurrahman; Siti Nurwahidah Lubis (Academic Solution Publisher, 2026)
This article reviews the role of interpersonal communication in improving the effectiveness of student–lecturer relationships in higher education. Using a narrative literature review approach, the study synthesizes five selected journal articles published between 2021 and 2025 that discuss lecturer–student communication, academic supervision, learning motivation, and student engagement. The findings indicate that interpersonal communication functions as a crucial relational mechanism in shaping academic trust, participation, emotional comfort, and learning effectiveness. Five major dimensions consistently emerged from the reviewed studies, namely openness, empathy, supportiveness, positive attitude, and equality. These dimensions contribute to the creation of a conducive academic environment in which students feel respected, motivated, and encouraged to participate actively. The review also shows that communication becomes increasingly important in vulnerable contexts such as thesis supervision and distance learning. Overall, interpersonal communication is not merely a supporting element of teaching, but a central factor in strengthening the quality of student–lecturer relationships.